Longitudinal changes in brain function associated with symptom improvement in youth with PTSD. (July 2019) - Garrett, Amy; Cohen, Judith A.; Zack, Sanno; Carrion, Victor; Jo, Booil; Blader, Joseph; Rodriguez, Alexis; Vanasse, Thomas J.; Reiss, Allan L.; Agras, W. Stewart
Abstract: Background: Previous studies indicate that youth with posttraumatic stress disorder (PTSD) have abnormal activation in brain regions important for emotion processing. It is unknown whether symptom improvement is accompanied by normative changes in these regions. This study identified neural changes associated with symptom improvement with the long-term goal of identifying malleable targets for interventions. Methods: A total of 80 functional magnetic resonance imaging (fMRI) scans were collected, including 20 adolescents with PTSD (ages 9–17) and 20 age- and sex-matched healthy control subjects, each scanned before and after a 5-month period. Trauma-focused cognitive behavioral therapy was provided to the PTSD group to ensure improvement in symptoms. Whole brain voxel-wise activation and region of interest analyses of facial expression task data were conducted to identify abnormalities in the PTSD group versus HC at baseline (BL), and neural changes correlated with symptom improvement from BL to EOS of study (EOS). Results: At BL, the PTSD group had abnormally elevated activation in the cingulate cortex, hippocampus, amygdala, and medial frontal cortex compared to HC. From BL to EOS, PTSD symptoms improved an average of 39%. Longitudinal improvement in symptoms of PTSD was associated with decreasing activation in posterior cingulate, mid-cingulate, and hippocampus, while improvement in dissociative symptoms was correlated with decreasing activation in the amygdala. Conclusions: Abnormalities in emotion-processing brain networks in youth with PTSD normalize when symptoms improve, demonstrating neural plasticity of these regions in young patients and the importance of early intervention.